A SURVEY OF FUZZY C-MEANS BASED ALGORITHMS FOR SEGMENTATION OF BRAIN MAGNETIC RESONANCE IMAGES - Nazir, Nighat (International journal of advanced research in computer science, 2018)
Abstract-Brain tissue segmentation aims to segment different tissues such as white matter (WM), gray matter (GM), and cerebrospinal fluid (CSF) from magnetic resonance images (MRI). In the past, many researchers have proposed MRI segmentation techniques in the field of medical image and soft computing. A number of segmentation techniques have been proposed among them thresholding, region-based segmentation, classification-based segmentation are the mostly used technique. In this paper, a comprehensive overview of fuzzy C-means (FCM) based algorithms for MRI segmentation is presented.